Serpent Handling: Toward a Cognitive Account – Honoring the Scholarship of Ralph W. Hood Jr - Coleman, Thomas J. (Journal of cognition and culture, 2021)
The ritual handling of serpents remains an unnoticed cultural form for the explanatory aims and theoretical insights desired by cognitive scientists of religion. In the current article, we introduce the Hood and Williams archives at The University of Tennessee at Chattanooga that contains data culled from Hood’s 40-plus year career of studying serpent handlers. The archives contain hundreds of hours of interviews and recordings of speaking in tongues, handling fire, drinking poison, and taking up serpents by different congregants and congregations. The archive remains a rich but untapped source of data for building, testing, and refining cognitive theories of ritual in general, and serpent handling in specific. We connect Hood’s work to current cognitive theories and engage critically with research on the social functions of ritual. Finally, we discuss several further reasons to pay more attention to SHS communities and practices in cognitive theories of ritual.